Legal Protection for Informal Workers in Indonesia - Najma Syamila; Tundjung Herning Sitabuana (Jurnal Daulat Hukum, 2025)
The Indonesian Constitution, as well as the highest legal basis, the 1945 Constitution, contains the rights of every citizen. These include the right to obtain decent work and legal protection, as stated in Article 27 paragraph (2) and Article 28D paragraph (1) and paragraph (2). The current Employment Law, as the legal basis for employment in Indonesia, still limits worker qualifications only based on work agreements as regulated by the Employment Law. In fact, the workforce population in Indonesia is currently dominated by informal workers, which has an impact on informal workers who are still far from access to legal protection due to the current legal instruments that limit worker categories. This study examines legal protection for informal workers in Indonesia. This study is a normative legal study, examining legal norms using theories including the legal protection theory put forward by Satipdjo Rahardjo. The results of the analysis indicate a legal vacuum in the protection of informal workers, so that changes are needed in the legal system and policies to create special regulations that can explain the rights and obligations of informal workers, as well as provide a clear legal status